Highly Efficient Hybrid Polymer and Amorphous Silicon Multijunction Solar Cells with Effective Optical Management - Tan, Hairen (Advanced materials (Deerfield Beach, Fla.), 2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.